Higiene Sanitasi, Kandungan Escherichia coli Air Baku dan Air Minum pada Depot Air Minum (DAM) di Kelurahan Sumbersari - Dwi Hanum Al Azmi (Fakultas Kesehatan Masyarakat, 2025)
Sumbersari urban village has the most drinking water stations with 21 Drinking Water Stations compared to 7 other urban villages. However, based on the results of preliminary studies at the Jember District Health Office in the Public Health Unit, it was found that 21 drinking water stations operating in Sumbersari Village didn’t have a Certificate of Good Hygiene Sanitation. In addition, the sanitary inspection of drinking water stations carried out by the health center is only done by sampling so the sanitary hygiene of the entire drinking water stations is unknown. The health center officers only took routine samples once every 3 months on drinking water for examination of Total Coliform parameters while E. coli parameters in drinking water and raw water were not examined. Based on preliminary studies at 10 drinking water stations in Sumbersari Village, it was found that handlers didn’t implement hygiene practices such as not washing hands before serving consumers, sanitation facilities were not complete, and the condition of drinking water stations still didn’t meet sanitation principles. Therefore, the purpose of this study was to describe the sanitary hygiene of drinking water stations and to identify the content of Escherichia coli in raw and drinking water. The research used in this study was descriptive. This research was conducted at all drinking water stations in Sumbersari Village in March 2024. The population used in this study were all drinking water stations in Sumbersari Village with criteria that were willing to be interviewed and samples of drinking water and raw water were taken. The sampling technique used in this study used total sampling from 17 drinking water stations. Data collection techniques using laboratory tests, observation sheets, and interviews regarding drinking water station sanitation hygiene. The variables studied were sanitary hygiene including places, handlers and equipment as well as E. coli content in raw water and drinking water. Data analysis using univariate analysis to describe sanitary hygiene including xiii places, handlers and E. coli content in raw water and drinking water and presented in tabular form and narrated. Based on the results of the study, 82,4% of the hygiene of drinking water station handlers did not meet these requirements. This was because the handlers did not wear clothes that were only used in the workplace, did not wash their hands with soap or running water before serving consumers, did not have a health check at least once a year, and did not have a sanitation hygiene training certificate. The sanitation assessment of drinking water stations based on premises amounted to 41,2 % of the drinking water stations that did not meet the requirements. This was because the drinking water stations location was not free from dust or smoke pollution, there was no sink equipped with running water and soap, the ceiling was open, hollow, and humid, there was no air ventilation, and there was no closed trash can. While the sanitation assessment of drinking water stations based on equipment is 100% qualified, there are several components that are not good, such as dirty water taps, expired UV lamps, and no brushing on gallons. The E. coli content in raw water was identified in 8 drinking water stations, namely drinking water stations A, E, H, I, L, N, O and Q. The E. coli content in drinking water was identified at 2 drinking water stations, drinking water stations H and N. Suggestions that can be given to the Jember District Health Office include conducting sanitary hygiene training for drinking water station operators and imposing sanctions on drinking water stations that do not meet the requirements for physical fitness and water quality. Drinking water station owners/operators need to routinely replace UV lamps every 2-3 years, routinely check the quality of raw water and drinking water at least once every 3 months and complete drinking water station facilities and equipment such as hand washing stations equipped with running water and soap, trash cans that have lids and provide gallon scrubbers. The public should be more selective in choosing water refill stations by ensuring the presence of laboratory test results for drinking water quality, which are usually posted at the stations. Additionally, they can reprocess the drinking water from these stations by boiling it until it reaches a rolling boil.
Reaploud Repository April 2026
Keywords: sanitasi; Air minum; Air Baku